2021
DOI: 10.1177/1478077121992487
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the digital re-constructions of muqarnas systems: The case study of Sultanhanı muqarnas in Central Anatolia

Abstract: This paper presents a comparative case study on the digital modeling workflows of a particular muqarnas system. After the literature review and the definition of the context, several digital modeling workflows were described as element-based, tessellation-based and block-based workflows by using computer-aided design and parametric modeling software. As the case study of this research, these workflows were tested on a muqarnas design located at the Sultanhanı Caravanserai in Central Anatolia. Then, workflows w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Ferrer-Pérez-Blanco et al [173] provided a laser scanner to capture new drawings of the muqarnas, accurate plans, and elevations for the first time and documented the muqarnas' complex shapes from the fourteenth century. Dinçer and Yazar [174] compared different case studies for the digital modeling of muqarnas systems in which variations were developed by element-based, tessellation-based, and block-based workflow. More recently, Gokmen et al [175] focused on 12 unique muqarnas structures found in Anatolia that were analyzed through a computational methodology combining photogrammetry, three-dimensional modeling, symmetry, and graph theory.…”
Section: Aesthetic-based; Generation Methods and Variationsmentioning
confidence: 99%
“…Ferrer-Pérez-Blanco et al [173] provided a laser scanner to capture new drawings of the muqarnas, accurate plans, and elevations for the first time and documented the muqarnas' complex shapes from the fourteenth century. Dinçer and Yazar [174] compared different case studies for the digital modeling of muqarnas systems in which variations were developed by element-based, tessellation-based, and block-based workflow. More recently, Gokmen et al [175] focused on 12 unique muqarnas structures found in Anatolia that were analyzed through a computational methodology combining photogrammetry, three-dimensional modeling, symmetry, and graph theory.…”
Section: Aesthetic-based; Generation Methods and Variationsmentioning
confidence: 99%
“…The fusion of the terrain model and the terrain is achieved by using the local reconstruction of the terrain grid [40][41][42]. The fusion display of terrain and ground objects is achieved through the construction of a multi-level regular triangulation network, incorporation of a transition area, and implementation of dynamic scheduling for view LOD (Level of Detail) [43][44][45][46]. Most of the fusion methods presented above predominantly use feature line constraint fusion for single-scale scenes.…”
Section: Introductionmentioning
confidence: 99%